Colorectal Serrated Lesions: A Current View on Clinical, Morphological, Molecular, and Genetic Diagnostic Criteria - Mikhaleva, Liudmila M.; Vandysheva, Rositsa A.; Midiber, Konstantin Yu.; Vasyukova, Olesya A.; Pechnikova, Valentina V.; Patsap, Olga I.; Beylerli, Ozal; Somasundaram, Siva G.; Kirkland, Cecil E.; Aliev, Gjumrakch (Current Medicinal Chemistry, 2021)
Objective: Serrated colorectal lesions are a group of colonic lesions with a serrated (saw-tooth) profile of the surface epithelium and crypts, and peculiar molecular and genetic developmental mechanisms that are incompletely understood. These formations cause concern due to their premalignant potential. Aim: The review is dedicated to serrated lesions of colon and appendix. We focused on modern classification, role in carcinogenesis, as well as new approaches to morphological diagnosis. Methods: A literature search was performed using PubMed, Scopus, ResearchGate, Google, MEDLINE, and ScienceDirect databases to find studies of serrated colorectal lesions related cancer published between 2000 and 2020 that address epidemiological risk factors, underlying pathophysiological mechanism and enable our review of these factors as well as molecular, genetics, and structural patterns. Results: Serrated colorectal lesions take one third of all benign neoplasms of the colon in the pathologist’s practice. The active study of serrated lesions began in the 1900s. Terminology and diagnostic criteria changed in the updated classification in 2019. Morphological criteria, immunohistochemical and molecular profile, endoscopic and clinical characteristics are reviewed. Conclusion: Although significant efforts were made in attempt to improve our understanding and diagnostic criteria of serrated polyps of colorectum, very little has changed since the original morphologic description of preneoplastic serrated lesions in early 2000s. There remains a need for more research in order to develop more definitive immuophenotypic and molecular biomarkers in order to distinguish between non-neoplastic and neoplastic serrated lesions.
Keywords: neoplasm